Legal Processing to Adapt to Climate Change and Achieve Sustainable Development Goals - Ghafri, Hussain Said Saif Al; Fakhry, Wael Mahmoud; Emam, Maher Ibrahim Ebed (Journal of Cultural Analysis and Social Change, 2025)
Countries vary in capacity and historical emissions levels; although all countries and companies must work to reduce global emissions, not all countries will achieve net zero emissions at the same time, and developed countries have, over time, contributed more to the global stock of greenhouse gas emissions. The importance of research appears in highlighting the impact of treaties and constitutions on reducing carbon emissions and achieving sustainable development goals, in addition to the importance of the necessity of applying them in practice by focusing on the laws that Omani society needs to achieve sustainable development goals, as well as applying laws in practice to the internal level, and not only in terminology, literature and theoretical decisions. The research dealt with treaties and constitutions related to reducing carbon emissions and the emergence of what is known as climate litigation. The research concluded that developed countries should make every effort to reach net zero greenhouse emissions as soon as possible, and that developing and emerging countries need a longer time to achieve this goal, as they are developing their economies and strengthening their institutional capabilities. That time is not in everyone’s interest and reducing Emissions are not an option, but an urgent necessity.